Estado nutricional dos indígenas Pataxó de 5 aldeias de Minas Gerais, Brasil - Camila Medeiros da Silva Mazzeti (2015)
In the last Brazilian population census, individuals who declared themselves indigenous was 896 900, with 305 different ethnic groups. The social context of these peoples is marked by vulnerability. This is an epidemiological, cross-sectional and descriptive study in order to assessthe nutritional status, socio-demographic and economic profile, sanitation, and how to obtain food among indigenous Pataxó of 5 villages in Minas Gerais. The sample consisted of 294 individuals, of all ages, which were collected demographic, socioeconomic data, basic sanitation, obtaining food and anthropometric data (weight, height and waist circumference). The variables were collected through a questionnaire validated for the Brazilian indigenous population.Anthropometric measurements were collected following standards of the World Healt Organization, and the nutritional status was classified also according to the same entity being evaluated 255 individuals (87.4% of the population). A descriptive analysis (absolute and relative frequencies) and bivariate (chi-square and Fisher's exact test, Student's t-test and ANOVA) with significance level of 5% (p <0.05). It was observed that the population is young; despite high number of families recipients of social benefits, the relevant part had good living conditions as regards the type of material used in construction, access to electricity, regular garbage collection by municipalities and the fate of the waste was in septic tanks. Most families got their food, especially in regional markets and from production for family consumption (cultivation, animal husbandry and fisheries). There were no height and weight deficits in childhood and overweight prevalence rates were: 2.9% children (body mass index / age); adolescents 9.7% (Body Mass Index / age); adults - 48.1% in men and 64.3% in women (body mass index); elderly - 16.7% in men and 50.0% in women (body mass index). High prevalence of increased waist circumference was observed in adults and elderly individuals (90.3% women and 29.9% men). Was favorable nutritional profile in childhood and high prevalence of overweight and central fat since adolescence. A favorable demographic profile was also observed, with access to services such as electricity and garbage collection, housing in good condition, however, the conditions of sanitation, especially in relation to water treatment still need improvements and expansion. Thisstudy aims to contribute for public policies of health and food safety and extend discussions on indigenous health and nutrition in the country.